A Hydrologic Model for Studying the Climate Change Impact on Evapotranspiration and Water Yield in a Humid Tropical Watershed - Nabi, Amjad (1998)
A procedure for estimating the impact of CO2-induced climate and vegetation changes on actual evapotranspiration (ET), soil moisture and water yield in a humidtropical vegetated watershed was proposed and evaluated. A distributed parameter modelling approach was used whereby a watershed was subdivided into relatively homogeneous ground response units (GRUs) to provide distributed parameter capabilities. A distributed parameter ET submodel was developed based on a biophysical approach for simulating actual evapotranspiration from a watershed with closed canopy cover of natural and planted vegetation. The hydrologic model, called humid tropical vegetation climate hydrologic model (HTVCHM), was developed by incorporating this ET submodel. Leaf area index (LA!) was used in the model as a measure of vegetation structure and to quantify energy and mass exchange of canopies. The potentials of Landsat TM image was studied for LA! estimation using vegetation-index (VI) of rainforest, rubber and oil palm plantation. Canopy conductance (reciprocal of resistance) was also an important vegetative parameter which was included to represent CO2-induced changes in vegetation. A procedure was presented and evaluated for subdividing a watershed into GRUs through the application of an unsupervised pattern recognition algorithm in conjunction with topographic data to Landsat Thematic Mapper (TM) data in a GIS environment. To conduct the sensitivity analyses, climate and vegetation change scenarios were proposed based on the GCM prediction for this region and information from the literature. The procedure developed in this research is an effective and practical integrated approach to modelling the effects of climate and vegetation changes on the hydrologic response of watershed in this region. This procedure was applied and evaluated on the Trolak watershed of the Bernam River basin with a wet humid tropical climate and located in the south-east of Perak State of West Malaysia.